A new species of the genus Meiyingia Holzchuh, 2010 (Coleoptera, Cerambycidae, Cerambycinae) from China - Li, Zhu; Tian, Lichao; Chen, Li (Zootaxa, 2015)
The genus Meiyingia Holzchuh, 2010 presently consists of only one species, Meiyingia paradoxa Holzchuh, 2010 from Henan and Shaanxi, China. The genus is characterized by following characters: Head concave between antennal tubercles; clypeus narrow; frons flattened. Eyes small, finely faceted, divided with two lobes widely separated. Antennae slender; those of males longer than the body, with spines at basal antennomeres; third antennomere longest, eleventh antennomere shorter than previous ones. Pronotum slightly longer than broad. Stridulatory organ without median groove. Elytra soft, membranous and narrowed posteriorly with apex rounded; disc flattened. Legs very short, femora gradually widened, tibiae long; first hind tarsal segment longer than following two combined. Procoxal cavity widely open. Prosternal process very short, narrow and deep. Metacoxal cavity open to mesepimeron. Second to fourth sternites pressed in the middle, sternites remarkably long and densely hairy medially. The first four sternites laterally with greater dent.